Impact of RNA degradation on fusion detection by RNA-seq. (December 2016) - Davila, Jaime; Fadra, Numrah; Wang, Xiaoke; McDonald, Amber; Nair, Asha; Crusan, Barbara,; Wu, Xianglin; Blommel, Joseph; Jen, Jin; Rumilla, Kandelaria; Jenkins, Robert; Aypar, Umut; et al.
Abstract Background RNA-seq is a well-established method for studying the transcriptome. Popular methods for library preparation in RNA-seq such as Illumina TruSeq® RNA v2 kit use a poly-A pulldown strategy. Such methods can cause loss of coverage at the 5′ end of genes, impacting the ability to detect fusions when used on degraded samples. The goal of this study was to quantify the effects RNA degradation has on fusion detection when using poly-A selected mRNA and to identify the variables involved in this process. Results Using both artificially and naturally degraded samples, we found that there is a reduced ability to detect fusions as the distance of the breakpoint from the 3′ end of the gene increases. The median transcript coverage decreases exponentially as a function of the distance from the 3′ end and there is a linear relationship between the coverage decay rate and the RNA integrity number (RIN). Based on these findings we developed plots that show the probability of detecting a gene fusion ("sensitivity") as a function of the distance of the fusion breakpoint from the 3′ end. Conclusions This study developed a strategy to assess the impact that RNA degradation has on the ability to detect gene fusions by RNA-seq.